Flexibility in Adaptation Planning : When, Where and How to Include Flexibility for Increasing Urban Flood Resilience - Radhakrishnan, Mohanasundar (Netherlands : CRC Press, 2017)
"The magnitude and urgency of the need to adapt to climate change is such that addressing it has been taken up by the United nation's as one of the sustainable development goals - Goal 13 (SDG13) in 2015. SDG13 emphasises the need to strengthen resilience and adaptive capacity to climate related hazards and natural disasters. Coping with urban floods is one of the major needs of climate adaptation, where integration of climate change responses into flood risk management policies, strategies and planning at international, national, regional and local levels is now the norm. However, much of this integration lacks effectiveness or real commitment from stakeholders involved in adaptation planning and implementation. Hence this research has focused on integrating flexibility based adaptation responses into an urban flood risk management context. The research has synthesised flexible adaptation practices from several disciplines including information technology, automobile and aerospace manufacturing. The outcomes of the research are brought together in a framework for structuring local adaptation responses and an adaptation planning process based on flexibility concepts. The outcomes provide a way to assist with the identification of the appropriate nature and type of flexibility required; where flexibility can best be incorporated; and when is the most appropriate time to implement the flexible adaptation responses in the context of urban flooding."--Provided by publisher.
chapter 1 Introduction / Mohanasundar Radhakrishnan -- chapter 2 Structuring Climate Adaptation Through Multiple Perspectives: Framework And Case Study On Flood Risk Management / Mohanasundar Radhakrishnan -- chapter 3 Coping Capacities For Improving Adaptation Pathways For Flood Protection In Can Tho, Vietnam / Mohanasundar Radhakrishnan -- chapter 4 Context specific adaptation grammar for climate adaptation in urban areas / Mohanasundar Radhakrishnan -- chapter 5 Flexible adaptation planning for water sensitive cities / Mohanasundar Radhakrishnan -- chapter 6 Flexible adaptation planning in a water sensitive Melbourne / Mohanasundar Radhakrishnan -- chapter 7 Operationalising flexibility: Agile urban planning process / Mohanasundar Radhakrishnan -- chapter 8 Conclusions / Mohanasundar Radhakrishnan.
Submitted in fulfilment of the requirements of the Board of Doctorates of Delft University of Technology and of the Academic Board of the UNESCO-IHE Institute for Water Education for the degree of Doctor to be defended in public on Wednesday, 22nd November 2017, at 10:00 hours in Delft, the Netherlands.
Includes bibliographical references.
Keywords: Climatic changes -- Government policy; Flood control; Sustainable development